The role of gamification in shaping the brand loyalty of Generation Z consumers - Weits, Elkin (Graduate School of Business (GSB), 2026)
The study investigated the role of gamification in shaping the brand loyalty of Generation Z consumers in the South African context. Generation Z is known to be a demographic that is digitally savvy and wants innovative brand interactions. The study examined different brands that adopted gamification and created brand loyalty, consumer engagement, and the extrinsic and intrinsic motivational factors that drove brand interactions among South African Generation Z consumers. The study was guided by the self-determination theory by Ryan and Deci (2000) which looks at intrinsic motivation through the psychological needs for autonomy, competence and relatedness. The research employed a qualitative approach whereby 15 South African Generation Z participants were interviewed through semi-structured interviews. The study also adopted a phenomenological design to capture the lived experiences of South African Generation Z with gamification in their brand interactions. The study used a thematic analysis to extract insights from the engagement, loyalty and motivational drivers of South African Generation Z from their lived experiences with gamification. The findings of the study revealed that gamification fosters emotional, behavioural and cognitive engagement with brands, which shapes brand loyalty. Extrinsic motivation through monetary value from gamification were primary drivers of motivation, while competence, relatedness and autonomy were drivers of intrinsic motivation. The study concluded that gamification strategies of brands can enhance both extrinsic and intrinsic motivation of Generation Z. Brands therefore have to adopt tangible rewards with intrinsic motivators to sustain engagement with Generation Z consumers. The research contributes to the literature of gamification and brand loyalty, in an underexplored South African Generation Z market. The study offers practical insights for practitioners to leverage gamification to meet the unique consumer preferences of Generation Z, and serves as a foundation for future studies on gamification and marketing in South Africa.